2014
DOI: 10.1186/1475-2875-13-417
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ivermectin mass drug administration for malaria transmission control across different West African environments

Abstract: BackgroundMass drug administration (MDA) of ivermectin to humans for control and elimination of filarial parasites can kill biting malaria vectors and lead to Plasmodium transmission reduction. This study examines the degree and duration of mosquitocidal effects resulting from single MDAs conducted in three different West African countries, and the subsequent reductions in parity and Plasmodium sporozoite rates.MethodsIndoor-resting, blood-fed and outdoor host-seeking Anopheles spp. were captured on days surro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
137
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(149 citation statements)
references
References 27 publications
(36 reference statements)
11
137
0
Order By: Relevance
“…arabiensis than control cattle for up to 1 week post-treatment. Like orally-treated cattle, many previous studies found that orally-treated humans reduced the survival of Anopheles mosquitoes for at least 1 week [35, 40, 42, 44, 85]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…arabiensis than control cattle for up to 1 week post-treatment. Like orally-treated cattle, many previous studies found that orally-treated humans reduced the survival of Anopheles mosquitoes for at least 1 week [35, 40, 42, 44, 85]. …”
Section: Discussionmentioning
confidence: 99%
“…The effects of ivermectin on digestion of blood meal in the stomach of surviving mosquitoes suggests that it may also inhibit establishment of parasite development in mosquitoes [37]. In contrast, the MDA to humans contributed to decreased malaria transmission by reducing survival of wild Anopheles mosquitoes for 1 week that consequently shifted age structure to young females (less infectious mosquitoes), and reduced sporozoite rates for at least 2 weeks [39, 44, 45]. Therefore, the long lasting effects of ivermectin-treated cattle could similarly reduce the vectorial capacity of An.…”
Section: Discussionmentioning
confidence: 99%
“…Mass drug administration of IVM is effective at killing A. gambiae mosquitoes Alout et al, 2014), inhibiting P. falciparum sporogony in A. gambiae and disrupting malaria parasite transmission in endemic villages (Kobylinski et al, 2011;Alout et al, 2014). Thus, IVM mass drug administration has strong potential to be developed as a novel tool for malaria parasite transmission control.…”
Section: Discussionmentioning
confidence: 99%
“…IVM, when imbibed by vectors from host-treated blood meals, has proven to efficiently kill or disable A. gambiae s.s. both in the lab and in the field Sylla et al, 2010). More recently, IVM mass drug administration in multiple locations across West Africa has been shown to temporarily reduce the proportion of Plasmodium falciparum-infected A. gambiae in IVM-treated villages (Kobylinski et al, 2011;Alout et al, 2014). Sub-lethal doses of IVM have also been shown to inhibit the sporogony of P. falciparum in A. gambiae s.s. and impair coordinated flight patterns (Butters et al, 2012;Kobylinski et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in 3 different West African transmission settings, this same dose reduced An. gambiae survivorship by 33.9% for 1 week, their parity rates for more than two weeks, and sporozoite rates by more than 77% for 2 weeks [18]. …”
Section: Introductionmentioning
confidence: 99%